Cost-efficiency of specialist hyperacute in-patient rehabilitation services for medically unstable patients with complex rehabilitation needs: a prospective cohort analysis. Issue 9 (8th September 2016) - Turner-Stokes, Lynne; Bavikatte, Ganesh; Williams, Heather; Bill, Alan; Sephton, Keith
Abstract : Objectives: To evaluate functional outcomes, care needs and cost-efficiency of hyperacute (HA) rehabilitation for a cohort of in-patients with complex neurological disability and unstable medical/surgical conditions. Design: A multicentre cohort analysis of prospectively collected clinical data from the UK Rehabilitation Outcomes Collaborative (UKROC) national clinical database, 2012–2015. Setting: Two HA specialist rehabilitation services in England, providing different service models for HA rehabilitation. Participants: All patients admitted to each of the units with an admission rehabilitation complexity M score of ≥3 (N=190; mean age 46 (SD16) years; males:females 63:37%). Diagnoses were acquired brain injury (n=166; 87%), spinal cord injury (n=9; 5%), peripheral neurological conditions (n=9; 5%) and other (n=6; 3%). Intervention: Specialist in-patient multidisciplinary rehabilitation combined with management and stabilisation of intercurrent medical and surgical problems. Outcome measures: Rehabilitation complexity and medical acuity: Rehabilitation Complexity Scale—version 13. Dependency and care costs: Northwick Park Dependency Scale/Care Needs Assessment (NPDS/NPCNA). Functional independence: UK Functional Assessment Measure (UK FIM+FAM). Primary outcomes: (1) reduction in dependency and (2) cost-efficiency, measured as the time taken to offset rehabilitation costs by savings in NPCNA-estimated costs of on-going care in the community. Results: The mean length of stay was 103 (SD66) days. Some differences were observed between the two units, which were in keeping with the different service models. However, both units showed a significant reduction in dependency and acuity between admission and discharge on all measures (Wilcoxon: p<0.001). For the 180 (95%) patients with complete NPCNA data, the mean episode cost was £77 119 (bootstrapped 95% CI £70 614 to £83 894) and the mean reduction in 'weekly care costs' was £462/week (95% CI 349 to 582). The mean time to offset the cost of rehabilitation was 27.6 months (95% CI 13.2 to 43.8). Conclusions: Despite its relatively high initial cost, specialist HA rehabilitation can be highly cost-efficient, producing substantial savings in on-going care costs, and relieving pressure in the acute care services.